From adversity to achievement: Supriya Das pioneers mechanized seeding and women’s empowerment in Odisha - Mohapatra, Bidhan; Kumar, Ashok; Kumar, Virender (International Rice Research Institute, 2025)
Mrs. Supriya Das, a 49-year-old woman farmer from Bada Gumula village in Ganjam district, Odisha, has set a remarkable example of innovation and empowerment in agriculture. With the support of the IRRI and Government of Odisha Direct-Seeded Rice in Odisha (IRRI-GoO-DSR-Odisha) Project, she is revolutionizing the way her village approaches farming by championing mechanized seeding of rice and sequential crops layered with potential varieties/hybrids and tailored agronomy, and also scaling the innovations. In addition to agriculture, Supriya also leads women’s empowerment through socio-political interventions.